Endoscopic Resection of Zenker's Diverticulum. Issue 2 (2001) - Kataoka, Hideyuki; Kitano, Hiroya; Fujimura, Masaki; Hirano, Masamitsu; Kinoshita, Takashi; Hanada, Makoto; Kasuya, Norikuni; Kitajima, Kazutomo
Abstract : We report an endoscopically assisted total diverticulectomy for Zenker's diverticulum. Skin incisions were made at the anterior axillary line, the center of the sternum, and the neck as portals for endoscopical instruments. The skin was retracted with hooks which provided an excellent view of the working space. The diverticulum was fully exposed and resected by using a multifire endoscopic stapler. This approach is minimally invasive in comparison with the conventional open cervical approach.